INFLUENCE OF LOCAL CULTURE ON QUALITY EMPLOYEE WORK AT PT. HADJI KALLA TOYOTA CITY PAREPARE - Rusmin Nuryadin; Yadi Arodhiskara; Sisni Miayu (DECISION : Jurnal Ekonomi dan Bisnis, 2023)
This study aims: Hadji Kalla Toyota Parepare Branch (2) To find out the effect the meaning of the local cultural value "Awaraniang (Courage)" influences the quality of work at PT. Hadji Kalla Toyota Parepare Branch; To find out whether the meaning of the Local Cultural values "Lempu (Honesty) and Awaraniang (Courage)" and if they jointly influence the Quality of Work at PT. Hadji Kalla Toyota Parepare Branch. The method used is Quantitative Descriptive. The results obtained from this study The value of local wisdom in the Bugis community, especially related to the meaning of Lempu, is considered to have an influence but not significant on improving the quality of work of PT. Hadji Kalla Parepare Branch. This can be explained that Lempu in its category is an adjective, even though it is an absolute part that must be owned by a human being, but because the frame owned can only be meaningful if it is followed by an action, so in this study, it is said to have an influence but not significant if it is not supported application in the form of action. The values contained in Warani besides being interpreted as having the will or determination to do the best thing possible, the meaning of warani itself, when examined from the point of view of the Bugis philosophy, contains things that are an absolute requirement as a human being, namely values. honesty. The results of the analysis provide reinforcement that Warani's attitude has a very significant influence on improving the quality of work is based on the values contained in Siri' and Pangadereng, Awaraniang, and Lempu are one devotion that cannot be separated because the two of them support and are bound to each other. So that the results of the analysis obtained show that together these two values of local Bugis human wisdom will have a very significant influence on improving the quality of work.